Safeguarding human–wildlife cooperation - Jessica E. M. van der Wal; Claire N. Spottiswoode; Natalie T. Uomini; Mauricio Cantor; Fábio G. Daura‐Jorge; Anap I. Afan; Mairenn C. Attwood; Jenny Amphaeris; Fatima Balasani; Colleen M. Begg; Cameron J. Blair; Judith L. Bronstein; et al. (Conservation Letters, 2022)
Abstract Human–wildlife cooperation occurs when humans and free‐living wild animals actively coordinate their behavior to achieve a mutually beneficial outcome. These interactions provide important benefits to both the human and wildlife communities involved, have wider impacts on the local ecosystem, and represent a unique intersection of human and animal cultures. The remaining active forms are human–honeyguide and human–dolphin cooperation, but these are at risk of joining several inactive forms (including human–wolf and human–orca cooperation). Human–wildlife cooperation faces a unique set of conservation challenges, as it requires multiple components—a motivated human and wildlife partner, a suitable environment, and compatible interspecies knowledge—which face threats from ecological and cultural changes. To safeguard human–wildlife cooperation, we recommend: (i) establishing ethically sound conservation strategies together with the participating human communities; (ii) conserving opportunities for human and wildlife participation; (iii) protecting suitable environments; (iv) facilitating cultural transmission of traditional knowledge; (v) accessibly archiving Indigenous and scientific knowledge; and (vi) conducting long‐term empirical studies to better understand these interactions and identify threats. Tailored safeguarding plans are therefore necessary to protect these diverse and irreplaceable interactions. Broadly, our review highlights that efforts to conserve biological and cultural diversity should carefully consider interactions between human and animal cultures. Please see AfricanHoneyguides.com/abstract‐translations for Kiswahili and Portuguese translations of the abstract.